Intraoperative Neurophysiological Monitoring in Contemporary Spinal Surgery: A Systematic Review of Clinical Outcomes and Cost-Effectiveness - Luca Zanin; Laura Broglio; Pier Paolo Panciani; Riccardo Bergomi; Giorgia De Rosa; Luca Ricciardi; Giusy Guzzi; Alessandro Fiorindi; Carlo Brembilla; Francesco Restelli; Francesco Costa; Nicola Montemurro; et al. (Brain Sciences)
Background: Intraoperative neurophysiological monitoring (IONM) is increasingly used during spinal surgery to reduce the risk of neurological complications. This systematic review evaluates both the clinical outcomes and cost-effectiveness of IONM in contemporary spinal surgery. Methods: A comprehensive literature search was conducted to identify studies evaluating IONM in spinal surgery. Twenty-three studies were included: twenty-one reporting clinical outcomes and two focusing on economic analysis. Data on neurological deficits, monitoring accuracy, and cost-effectiveness were extracted and analyzed. Results: Analysis of the included studies showed that IONM reduced the risk of neurological deficits across various types of spinal surgery. The diagnostic accuracy varied by modality, with MEP showing the highest sensitivity (90.2%) and SSEP demonstrating high specificity (97.1%). The greatest benefit was observed in deformity surgery and spinal tumors. D-wave monitoring showed efficacy for intramedullary tumors. Economic analysis demonstrated that IONM is cost-effective when the neurological complication rate exceeds 0.3%, with potential savings of over USD 23,000 per case. Conclusions: IONM significantly improves neurological outcomes in spinal surgery and is cost-effective in most clinical scenarios, particularly in high-risk procedures. Multimodal monitoring approaches provide the most comprehensive neurological assessment. These findings support the routine use of IONM in contemporary spinal surgery, especially for complex cases.